Pictorial Referents Facilitate Recognition and Retrieval Speeds of Associations Between Novel Words in a Second Language (L2) and Referents - Liu, Xinyi; Horinouchi, Hiroki; Yang, Yutao; Yan, Yan; Ando, Misa; Obinna, Ukwueze Jonah; Namba, Shushi; Kambara, Toshimune (Frontiers in Communication, 2021)
This study reveals associative processes for novel words in a second language (L2) and their referents. Thirty Japanese participants learned associative pairs for novel words in Chinese and pictorial referents (CP), as well as novel words in Chinese and words in Japanese (CJ), against a condition in which they learned only novel words in Chinese (C). After the learning phase, participants conducted two learning condition retrieval tasks for word recognition and three recognition tasks for the source-monitoring of the referents. The correct answers for each recognition task were provided to participants after each trial. Although the correct answers in all conditions increased in both the recognition and learning condition retrieval tasks, there was no significant difference among conditions. In contrast, the response times of the correct trials in all recognition tasks and the first learning condition retrieval tasks were faster for the CP condition than the CJ condition. Third, in the second learning condition retrieval task, missed items in associative conditions (CP and CJ conditions) were judged to be learned items more often than unlearned items, whereas missed items in the non-associative condition (C condition) were judged unlearned items more than learned items. These findings suggest that pictures contribute to the recognition and retrieval speed of associations between novel words in L2 and referents, and that associative learning of L2 words and referents could enhance more familiarity effects than the learning of L2 words only.